Targeting plasma cells with daratumumab aids in the treatment of post‐transplant autoimmune‐like hepatitis. Issue 11 (13th August 2021) - Epperly, Rebecca; Santiago, Teresa; Morin, Cara E.; Patton, Kurt; Deyo, Jeff; Eshun, John; Triplett, Brandon; Sharma, Akshay
Abstract: Antibody‐mediated autoimmune‐like hepatitis is a rare and challenging occurrence after hematopoietic cell transplant (HCT). We present the case of a 16‐year‐old male patient with Ph+ ALL who underwent matched sibling donor HCT and developed autoimmune‐like hepatitis after receiving ponatinib for post‐HCT maintenance, evidenced by marked plasma cell infiltrate on liver biopsy. He was successfully treated with steroids and daratumumab, an anti‐CD38‐monoclonal antibody. The dramatic response in this patient warrants expanded investigation of daratumumab for plasma cell‐mediated disorders post‐HCT. It further highlights that identifying mechanisms of immune‐mediated injury can allow for directed therapy and limit exposure to broad immune suppression.